PENGARUH PROFITABILITAS, TANGIBILITAS, UKURAN PERUSAHAAN, DAN PERPUTARAN ASET TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERCATAT DI BEI - Farhan Nailul Firdaus; Syarifah Rahmawati (Departemen Manajemen, 2021)
This study aims to determine the effect of profitability, tangibility, company size, and asset turnover on capital structure in property and real estate companies listed on the Indonesia Stock Exchange (IDX). This study uses panel data with 27 Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) from the 2014-2018 period. The analytical method used is multiple regression analysis with fixed effect models. Partially the results of the study show that profitability has a negative and significant effect on capital structure, tangibility has no effect on positive direction on capital structure, company size has a positive and significant effect on capital structure, and asset turnover has no effect on positive direction on capital structure on property companies and real estate in Indonesia. In this study only profitability is in line with the pecking order theory. While the variable tangibility, and company size are in line with the trade-off theory.